Crystallization and preliminary crystallographic analysis of a surface antigen glycoprotein, SAG19, from Eimeria tenella - Ramly N.Z.; Rouzheinikov S.N.; Sedelnikova S.E.; Baker P.J.; Chow Y.-P.; Wan K.-L.; Nathan S.; Rice D.W. (2024)
Coccidiosis in chickens is caused by the apicomplexan parasite Eimeria tenella and is thought to involve a role for a superfamily of more than 20 cysteine-rich surface antigen glycoproteins (SAGs) in host-parasite interactions. A representative member of the family, SAG19, has been overexpressed in Escherichia coli, purified and crystallized by the hanging-drop method of vapour diffusion using ammonium sulfate as the precipitant. Crystals of SAG19 diffracted to beyond 1.50 resolution and belonged to space group I4, with unit-cell parameters a = b = 108.2, c = 37.5. Calculation of possible values of V M suggests that there is a single molecule in the asymmetric unit. 2013 International Union of Crystallography.